Data Model and Software Architecture for Business Process Model Generator - Ivaylo Kamenarov; Katalina Grigorova (JOIV : International Journal on Informatics Visualization, 2018)
This paper describes the internal data model for a business process generator. Business process models are stored in an Event-driven process chain notation that provides a natural way to link the individual elements of a process. There is a software architecture that makes it easy to communicate with users as well as external systems.